ANALISIS PARTISIPASI PEREMPUAN DALAM PROSES PENCALONAN ANGGOTA LEGISLATIF PADA PEMILU2009 DI KABUPATEN PELALAWAN - Ratna Dewi dan Mustiqowati Ummul F (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
This studyaims to determinethe participation of women as legislative candidates on political partiesin the legislative Pelalawan and the factor sthatled tothe relatively low participation of womenwhorun for the legislative elections Pelalawan the districtin 2009.The results showed still low participation of womenin politics, name lythenomination of candidates forthe legislative elections of 2009 participantsin Pelalawan this looksratio of the numberof womencandidates for legislative members who are still less than30% quotaas set outin theLaw12in 2004in the electionof2009.In addition,data on the numberof candidatesinthe 2009 election legislators in Pelalawan as 479 people, only 137 people who are female candidates, while 342 people are male candidates. It is still under the provisions of30% quotafor female representation.So that the low participation of women it can be as certained that thenumberof womenwhohave theopportunitytobe involved inpublic policy-makingis alsoverylimited.This study used adescriptive analysis to describe the full reality of the fulfillment of thequota of 30% representation of womeninlegislative candidacyinthe 2009 electionin Pelalawan which has been describedin LawNo.12of 2012pasal65. From the research, based on theanswersof informantsabout the levelof for male education to which womenwho are candidates forthe legislativemajorityarehigh school graduates. Then basedonthe experienceof informantsanswerstating organization owned organization experienceis still low. Some claimedrecentlyin apolitical party and even there that has not beencompletelyenteredin the management ofpolitical parties. Recruitment systemis not yet fullyimplementedeitherbecause it is based informal system so thatwomenare not representedin the legislature, and consequently30% quota for womenin the legislatureis not reached, resulting in the aspirationsof womeninparliamentPelalawannot accommodated properly, then the patriarchalsocioculturalsystemstillview womenare lessable toplay a role inpolitical office, so that women are marginalizedin terms of bothformal and informal